Direito à água: contribuições para o acesso mais justo, equitativo e democrático à água - Moraes, Tatiana Vieira de (2025)
Water in quantity and quality is an essential human right, but a large portion of the population still does not have access to this right. SDG 6 sets the goal of universal and equitable access to water for all people by 2030 and, based on the hypothesis that the current Brazilian water management system does not sufficiently guarantee access to the right to water in an equitable and fair manner, this study aims to identify, based on case studies of water conflicts, various possibilities and potential actions, measures or principles with a view to contributing to fairer, more equitable and democratic access to the right to water. To this end, methodological pluralism was adopted, with each chapter addressing a set of specific methods and procedures. The study is presented in three parts: the first, more theoretical, proposes a literature review. At this point, the right to access water as an essential human right is discussed, pointing out the possibility of considering water as a fundamental right in Brazil, even without express constitutional provision. It also analyzes the Brazilian National Water Resources Policy and criticizes the conventional model of water resources management adopted in Brazil, especially its limitations in terms of participation and equity. This is followed by a discussion of effective water governance, highlighting the importance of a governance system that strengthens the participation of society. This part of the study concludes with theoretical clarifications on the concept of water equity, presenting definitions and basic elements, as well as differentiating equity from water justice. The second part examines case studies of water problems/conflicts. Adopting a narrow geographical approach, a survey was carried out of cases of international and national water conflicts in the literature; in the state of São Paulo through Civil Inquiries by the Public Prosecutor’s Office of São Paulo (MPSP); and a local case in the municipality of São Carlos/SP. The results of this part of the study were the mapping of water conflicts based on the cases examined and the potential of the measures and solutions suggested and/or applied to resolve or mitigate the conflicts. The third part of the study is propositional, presenting contributions to more equitable and democratic access to the right to water and interconnecting the first two parts. The analyses of the previous parts of the study demonstrate the existence of various inequalities in access to water and the inadequacy of the conventional water management system to sufficiently guarantee fair, democratic and equitable access to the right to water. As a result, contributory proposals were generated aimed at advancing the transition from the current water management format to a more effective system of ‘good water governance’ that promotes democratic, equitable and fair access to the right to water.